Research of business processes for a web-based information system for food storage control - Bondarenko, D. B.; Liutenko, Iryna Victorivna (Одеська національна академія харчових технологій, 2023)
The thesis discusses the importance and potential of information systems for refrigerated food accounting to reduce food loss, improve social and environmental performance, and increase resource efficiency. This article discusses the key aspects of such systems and their impact on society and the environment.
Keywords: business processes; web-based information; food storage control; Food and Agriculture Organization (FAO); world's food production; waste